Multiple sclerosis: etiology in the context of neurovascular unit and immune system involvement and advancements with in vitro blood–brain barrier models - El-Taibany, Aya A.; Heydarian, Parichehr; Porada, Daniel A.; Seeds, Michael C.; Atala, Anthony (Frontiers in Immunology, 2025)
Multiple sclerosis affects a significant portion of the world’s adult population and is the most common nontraumatic neuroimmunology disorder. Although the specific etiology of multiple sclerosis remains unknown, it has been associated with autoimmune components. While current treatment options relieve some symptoms in MS patients, most are immunosuppressive and only delay the progression of the disease without conferring definitive curative measures. Hence, a thorough understanding of disease pathobiology, the contribution of the neurovascular unit (NVU), and biological body-on-a-chip systems that replicate the blood–brain barrier may open new horizons for the discovery of potential therapeutics for MS.